THE SHIFT WORDS USED BY THE YOUNG GENERATION IN KOTO NAN AMPEK PAYAKUMBUH - Bunga Yolanda; Saunir Saun (Universitas Negeri Padang, 2017)
Today, many young people do not understand the words used by the older generation, so a lot of misunderstandings happen when older generation talking using the words this all happened because there is shift words used by young generation. Therefore, the purpose of this paper is to find the words that are no longer used by the younger generation in Koto Nan Ampek Payakumbuh and writer wanted to know what factors that cause these shift words. In writing this paper, the author was helped by several informants who can provide information about the words that no longer used by the younger generation in daily conversation. Then the authors classify the data according to the words classes. The shift words are lost because it was no longer use, this caused by several factors such as social factors, economic factors, political factors, demographic factors and attitude and value.